O-20 Developing a children's hospice nursing workforce to meet the changing needs of babies, children and young people. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Gold, Libby; Semple, Scott
Abstract : Background: The clinical needs of babies, children and young people with life-shortening illnesses continue to change as their care becomes more complex; and the workforce requires to adapt to this. Aim: The aim of the project was to design and implement a nursing workforce structure that would meet the current and future needs of the service. The objectives were to analyse the service against workforce establishments; anticipate future needs; identify new roles; and create career pathways. Approach: Focus groups involving care staff looked at how the needs of families were supported and what might change in the future. Families were consulted and professional visits to other children's services were carried out. Staff consultation and feedback also informed the model. The successful new structure changed roles for the majority of the nursing workforce and implementation commenced with the most senior nurse managers. Opportunities for internal recruitment were maximised and the number of staff affected overall was then minimised by moving systematically through each tier. Outcomes: Nursing is now under a single Director for Children and Families with two Associate Nurse Directors – one leading the nursing teams, the other responsible for quality assurance, service development and clinical learning. New, additionalnursing roles provide leadership at the point of care as well as career pathways. Improved senior nurse cover across seven days, ongoing clinical training and leadership development; has empowered nurses to respond more quickly to deteriorating children. Creative recruitment practices have been used to manage challenges in recruiting registered nurses. Innovative processes have been introduced to support those employees uncertain of the change. Conclusion: Other nursing services may wish to learn from our experiences of implementing a new structure that meets the changing needs of patients and has created a career pathway for our staff.